The Frustrated Nerds Project - Resources for Systems Administrators in Higher Education: A Resource Webliography. - Jessamyn Henninger; Susan Ward Aber (Issues in Science and Technology Librarianship)
Systems Architects and Information Technology administrators working in higher education help faculty, staff, and student computer users. Yet, who helps them? What resources do these professionals value? A case study was conducted using purposeful sampling and data collection through electronic interview to gather the preferred information-seeking methods and resources used by experienced computer systems professionals. Findings were consolidated and organized into a list of their recommended resources for researching solutions to the complex logistical problems that arise in the day-to-day support and administration of information technology at higher education institutions. This webliography is designed to aid systems administrators as well as librarians who serve an information-seeking, technology-savvy clientele. [ABSTRACT FROM AUTHOR]